Morts pour la France: Things and memory in the ‘destroyed villages’ of Verdun - Filippucci, Paola (Journal of material culture, 2020)
This article considers the power of things to affect how the past is remembered in the aftermath of mass violence, through the case of the ‘destroyed villages’ (villages détruits) of the battlefield of Verdun, theatre in 1916 of one of the most destructive battles of World War I. As well as causing mass military death, the battle also led to the ‘death’ of nine small villages, declared to have ‘died for France’ and incorporated into the post-war commemorative landscape of the battlefield. The article illustrates the 21st-century discourse and practices that surround the remains of these villages, from emplaced ruins to photographs and other documents. A century after the ‘death’ of the villages, people who identify as descendants of the original inhabitants gather at the sites and through these objects evoke their ancestors and the pre-war settlement, momentarily reconstituting a space that they can ‘inhabit’ physically, imaginatively and affectively. However, bids to restore a ‘village’ space and time are overwritten by the commemorative framework in which the sites and remains have been embedded for the past century, that identifies the ‘dead’ localities with the human Fallen and their history with the moment of their ‘death for France’. So, while the surviving traces of the former villages retain their power to affect and thus to evoke the pre-war, civilian past, their ability to produce a new memory for Verdun is limited by their incorporation into a memorial landscape dedicated to heroic military death for the nation. The physical expropriation of sites and vestiges during the post-war reconstruction of the battlefield and their preservation as tangible tokens of mass death has enduringly fixed and overdetermined their meaning, in a form of symbolic expropriation that limits their power to produce memory.